Lactate as Potential Mediators for Exercise-Induced Positive Effects on Neuroplasticity and Cerebrovascular Plasticity - Huang, Zhihai; Zhang, Yulan; Zhou, Ruixue; Yang, Luodan; Pan, Hongying (Frontiers in Physiology, 2021)
The accumulated evidence from animal and human studies supports that exercise is beneficial to physical health. Exercise can upregulate various neurotrophic factors, activate neuroplasticity, and play a positive role in improving and enhancing cerebrovascular function. Due to its economy, convenience, and ability to prevent or ameliorate various aging-related diseases, exercise, a healthy lifestyle, is increasingly popularized by people. However, the mechanism by which exercise performs this function and how it is transmitted from muscles to the brain remains incompletely understood. Here, we review the beneficial effects of exercise with different intensities on the brain with a focus on the positive effects of lactate on neuroplasticity and cerebrovascular plasticity. Based on these recent studies, we propose that lactate, a waste previously misunderstood as a by-product of glycolysis in the past, may be a key signal molecule that regulates the beneficial adaptation of the brain caused by exercise. Importantly, we speculate that a central protective mechanism may underlie the cognitive benefits induced by exercise.